Producing sustainability professionals : assessing graduate attributes in sustainability : final report. - Holdsworth, Sarah; Thomas, Ian; Sandri, Orana; Chester, Andrea; McLaughlin, Tricia (Australia. Dept of Education and Training (DET), 2019)
The 'Producing sustainability professionals: Assessing graduate attributes in sustainability study' developed a tool to identify how a sample of RMIT alumni apply RMIT's 'environmentally aware and responsible' graduate attribute (EAR GA) within their professional practice. This research sits within the broader graduate attributes project that has been undertaken across universities around the world (see Barrie 2012) and within research on sustainability and education, specifically understanding learning outcomes as a result of education and sustainability. A critical knowledge gap currently exists in the understanding of graduate learning outcomes and employability skills. Specifically, it is unclear how graduates are applying the attributes and skills developed through their degree programs, and if these are relevant in their workplaces. This project assessed the extent to which graduates understand, and can apply, sustainability attributes in the workplace. The project developed and evaluated a tool for the sector to aid assessment of sustainability attributes, and to inform learning and teaching strategies for addressing curriculum gaps identified through its application. The application of this tool provides a critical feedback loop to enable academics to understand how their teaching relates to the needs of employers and helps them to improve curriculum and graduate employability. The tool is applicable across the sector for the measurement of sustainability attributes in Australian university graduates, with potential application to graduate attributes in other areas. [Executive summary, ed]